Anti-inflammatory effects of anthocyanins-rich extract from bilberry (Vaccinium myrtillus L.) on croton oil-induced ear edema and Propionibacterium acnes plus LPS-induced liver damage in mice. (August 2014) - Luo, Hui; Lv, Xiao-Dan; Wang, Guo-En; Li, Yi-Fang; Kurihara, Hiroshi; He, Rong-Rong
Abstract Bilberry (Vaccinium myrtillus L.) has been known to play a protective role in human health due to its high anthocyanin content. This study investigated the anti-inflammatory effects of bilberry extract (BE, containing 42.04% anthocyanin) on Propionibacterium acnes (P. acnes) plus lipopolysaccharide (LPS) induced liver injury and croton oil-induced ear edema in mice. Results showed that BE could effectively inhibit croton oil-induced ear edema and liver inflammation provoked by P. acnes plus LPS, as reflected by the reduced plasma alanine aminotransferase and aspartate aminotransferase activities. These findings were confirmed by hepatic pathological examination. Moreover, BE administration markedly suppressed the increase of liver mRNA levels of iNOS, TNF-α, IL-1β and IL-6, and the protein levels of iNOS, TNF-α and NF-κB. In addition, liver malondialdehyde and NO contents were significantly reduced by BE treatment. These results indicated that BE has potent protective effects on acute and immunological inflammation, which might contribute to the study of the anti-inflammatory effects of natural products and healthy food.